Peran Budaya Literasi dalam Menumbuhkan Minat Baca dan Tulis - Errika Febi Lusianti (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the role of literacy activities in increasing students' interest in reading and writing. This research is qualitative research in the form of library research, namely a method of collecting data, understanding and researching theories from various scientific literature. Collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The research results show that literacy indirectly motivates students to be interested in reading and writing activities. From literacy activities, students are interested in taking part in writing, storytelling or reading competitions organized by the school with a high sense of responsibility. Literacy can provide benefits for students, for example increasing insight, making it easier to read and understand the material being studied. By building and maintaining a strong literacy culture, society can create an environment that supports and stimulates interest in reading and writing among all generations